2013
DOI: 10.1016/j.neulet.2012.11.063
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to measure upper extremity H-reflexes following neuromuscular electrical stimulation therapy after stroke

Abstract: Upper extremity (UE) hemiparesis persists after stroke, limiting hand function. Neuromuscular electrical stimulation (NMES) is an effective intervention to improve UE recovery, although the underlying mechanisms are not fully understood. Our objective was to establish a reliable protocol to measure UE agonist–antagonist forearm monosynaptic reflexes in a pilot study to determine if NMES improves wrist function after stroke. We established the between-day reliability of the H-reflex in the extensor carpi radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The H-reflex, obtained before exercise, was not modified by cerebral ischemia. This result was in agreement with a previous study on humans in which no difference of the extensor carpi radialis longus and flexor carpi radialis H-reflex in resting condition was detected after stroke injury [ 19 ] . Other study showed an opposite result by measuring an increase in H-reflex after stroke injury [ 18 ] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The H-reflex, obtained before exercise, was not modified by cerebral ischemia. This result was in agreement with a previous study on humans in which no difference of the extensor carpi radialis longus and flexor carpi radialis H-reflex in resting condition was detected after stroke injury [ 19 ] . Other study showed an opposite result by measuring an increase in H-reflex after stroke injury [ 18 ] .…”
Section: Discussionsupporting
confidence: 94%
“…The motor reflex regulation at the spinal level is recognized as an important aspect of the motor control and may be modulated by cerebral ischemia, despite the fact that controversial results remain for the upper-extremity control in human studies [ 16 ] [ 19 ] . The Hoffmann reflex (H-reflex) has often been used in preclinical human and animal studies to explore the spinal sensorimotor adaptation during and/or after skeletal muscle activity [ 20 ] , [ 21 ] .…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly assessed muscles of the lower limbs that display the H-reflex are the soleus muscle [37][38][39][40] and the gastrocnemius muscle [5,41,42]. While the H-reflex is very difficult to observe in the upper limbs, some researchers have shown that it can be induced for the flexor carpi radialis muscle [43][44][45][46][47] and the extensor carpi radialis muscle [43,46].…”
Section: Applications Of the Hoffman's Reflex Measurementmentioning
confidence: 99%
“…The H-reflex is frequently measured to assess the monosynaptic reflex in, among others, stroke patients [47] and healthy persons who do not engage in sport [39,55]. Researchers have also observed that sport training may affect the parameters of the H-reflex; hence, a growing number of studies in the literature are being conducted among athletes engaged in endurance sports [37], as well as in speed and strength sports [5,41].…”
Section: Applications Of the Hoffman's Reflex Measurementmentioning
confidence: 99%
“…While reflex inhibition has been used to assess rehabilitation effects [8], these findings were reported without information regarding its stability over time. Reproducibility of the FCR H-reflex latency, amplitude [14,15], and slope of the H-and Mwaves has been reported in healthy controls and persons poststroke [16,17], but the reliability of FCR H-reflex inhibition has not been established in either population.…”
Section: Introductionmentioning
confidence: 99%